SHS Students’ Engagement in Online Synchronous Collaborative Learning Activities: Correlations with Self-efficacy, Peer Social Support, Well-being and Academic Performance - Afable, Trisha Mae M.; Lamberto, Jilian Casandra D.; Ng, Trixia Anne Nicole P.; Umandap, Ashley Nicole S.; Arcinas, Myla M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The pandemic of COVID-19 prompted several paradigm shifts throughout society, including in education. This study aimed to examine the relationships of students' engagement in online synchronous collaborative learning activities (OSCLA) with their self-efficacy (LSE), peer social support (LPSS), state of well-being (SWB), and level of academic performance (LAP). A total of 176 Filipino Grade 12 SHS students, 18 years old and older, from a private educational institution were purposively selected for this study. Data were generated using an online survey. Results show that collaborative learning activities are frequently conducted (median = 4) in their synchronous online classes. It also revealed that their LSE is high (median = 4), their LPSS is high (median = 4), their LE is moderate (median = 3), their SWB is high (median = 4), and their LAP is high (median = 94.85). The results showed a statistically significant correlation of their LSE (r = 0.69, p 0.001) and LPSS with their OSCLA LE (r = 0.438, p 0.001). A statistically significant positive moderate correlation between LE and SWB (r = 0.536, p 0.001) was also found, however, no correlation was found between their OSCLA LE and LAP (r = 0.065, p = 0.393). Thus, the use of a well-designed OSCLA is strongly recommended as it positively impacts students' SWB but should be regularly reviewed for its effectiveness in sustaining improvement in the LAP of the students.